Cultural Learning Management in Increasing Creativity Of Students in Madrasah, State of Tsanawiyah 2 Jember - Istifadah Istifadah (Pancaran Pendidikan, 2018)
The teacher is the main component of the education system because the teacher can influence the quality of the educational process and outcomes. This research aimed to find out the lesson plan, learning implementation, learning evaluation, and supporting and inhibiting factors in improving students’ creativity. Research approach used was qualitative with descriptive method. Data were collected through interview, observation, and study documentation. Research subjects were principal, vice principal in the curriculum, Art and Culture teachers, and students. The results showed that: (1) planning was formulated based on curriculum 2013 and there were still some corrections to be improved. Planning was formulated by teachers in teaching administration such as syllabus, lesson plan, teaching and learning activities, annual program, semester program, effective time, and item analysis. (2) Learning implementation carried out by Art and Culture teacher was not implemented as stated in the lesson plan. (3) Leaning evaluation of Art and Culture subject was disorganized and assessment was not based on the follow-up a program. (4) The supporting factor of learning Art and Culture subject in improving students’ creativity was the internal factor from student itself. The inhibiting factors were insufficient facilities and infrastructures and lack of learning hours for cultural arts practices that fit the curriculum found in Extracurricular